2021
DOI: 10.1186/s13104-021-05501-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of maternity waiting homes on perinatal mortality is inconclusive: a critical appraisal of existing evidence from Sub-Saharan Africa

Abstract: Objectives To assess the appropriateness of the statistical methodology used in a recent meta-analysis investigating the effect of maternity waiting homes (MWHs) on perinatal mortality in Sub-Saharan Africa. Results A recent meta-analysis published in BMC Research Notes used a fixed-effect model to generate an unadjusted summary estimate of the effectiveness of MWHs in reducing perinatal mortality in Africa using ten observational studies (pooled o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Despite studies conducted revealing the use of Maternal Waiting Homes has a significant impact on reducing perinatal and maternal mortality ( 12 , 27 29 ), some studies conducted in Ethiopia revealed only 42.6% to 65.3% ( 28 30 ) pregnant women have intention to use Maternal Waiting Homes in their prospective delivery ( 31 ) while one study from the western part of Ethiopia revealed 38.7% of the study participants had experience in using Maternal Waiting Homes. Evidencing benefits of the use of Maternal Waiting Homes ( 12 , 27 29 ) to avert labor and delivery-related complications that may occur during labor and delivery and/or postpartum period is well established elsewhere ( 32 – 34 )…”
Section: Introductionmentioning
confidence: 99%
“…Despite studies conducted revealing the use of Maternal Waiting Homes has a significant impact on reducing perinatal and maternal mortality ( 12 , 27 29 ), some studies conducted in Ethiopia revealed only 42.6% to 65.3% ( 28 30 ) pregnant women have intention to use Maternal Waiting Homes in their prospective delivery ( 31 ) while one study from the western part of Ethiopia revealed 38.7% of the study participants had experience in using Maternal Waiting Homes. Evidencing benefits of the use of Maternal Waiting Homes ( 12 , 27 29 ) to avert labor and delivery-related complications that may occur during labor and delivery and/or postpartum period is well established elsewhere ( 32 – 34 )…”
Section: Introductionmentioning
confidence: 99%